Infrared Thermography in Wound Care, Surgery, and Sports Medicine: A Review - Ramirez-GarciaLuna, Jose L.; Bartlett, Robert; Arriaga-Caballero, Jesus E.; Fraser, Robert D. J.; Saiko, Gennadi (Frontiers in Physiology, 2022)
For many years, the role of thermometry was limited to systemic (core body temperature) measurements (e.g. pulmonary catheter) or its approximation using skin/mucosa (e.g., axillary, oral, or rectal) temperature measurements. With recent advances in material science and technology thermal measurements went beyond core body temperature measurements and found their ways in many medical specialties. The article consists of two primary parts. In the first part we overviewed current clinical thermal measurement technologies across two dimensions: a) direct vs. indirect and b) single-point vs. multiple-point temperature measurements. In the second part, we focus primarily on clinical applications in wound care, surgery, and sports medicine. The primary focus here is the thermographic imaging modality. However, other thermal modalities are included where relevant for these clinical applications. The literature review identified two primary use scenarios for thermographic imaging: inflammation-based and perfusion-based. These scenarios rely on local (topical) temperature measurements, which are different from systemic (core body temperature) measurements. Quantifying these types of diseases benefits from thermographic imaging of an area in contrast to single point measurements. The wide adoption of the technology would be accelerated by larger studies supporting the clinical utility of thermography.